Актуарная математика в современном мире - Исмуратова, Д.А. (My University, 2013)
Actuarial Mathematics – area of knowledge related to the application of mathematical calculations in insurance, including the likelihood of occurrence of the insured risk. The paper considers the application of Bernoulli to the problems of the theory of insurance.